PENGARUH GENDER, PENGALAMAN AUDITOR, KOMPLEKSITAS TUGAS, KEAHLIAN AUDITOR DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT (Studi Empiris pada Perwakilan BPKP Provinsi Riau) - Indriarta Hidayatunissa; Hardi Hardi; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of gender, auditor experience, task complexity, auditor expertise and compliance pressure on audit judgment at BPKP Riau Province. The data collection of this research was using questionnaire method that distributed to 98 auditors working at BPKP Riau Province. The numbers of auditors who became research sample were 70 auditors. Data analysis techniques used in this research was multiple linear regression analysis using SPSS 20 as data processing software program. The result of this research show that there is a significant relationship among gender, auditor experience, task complexity, auditor expertise and compliance pressure on audit judgment. The coefficient of determination (R²) shows that gender, auditor experience, task complexity, auditor expertise and compliance pressure simultaneously giving effect on audit judgment amounted to 72%. While the remaining 28% is influenced by other independent variable that are not observed in this research.Keywords : Gender, Auditor Experience, Task Complexity, Auditor Expertise and Compliance Pressure, Audit Judgment